PROBLEMS AND SOLUTIONS OF TRANSLATING MODAL UNITS IN ENGLISH AND UZBEK LITERARY TEXTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The translation of modal units in literary texts remains one of the most complex tasks in translation studies due to the semantic, pragmatic, and stylistic functions modality performs in language. Modal units express the speaker’s attitude toward reality, including notions of necessity, possibility, obligation, probability, and emotional evaluation. English and Uzbek differ significantly in the ways they encode modality, which creates serious challenges for translators. This article explores the main problems encountered in translating modal units between English and Uzbek literary texts and discusses possible solutions aimed at preserving meaning, stylistic nuance, and pragmatic intent. The study emphasizes the importance of contextual and functional approaches in achieving translation adequacy.